Sustainable tourism in Puraran Island: The case of the Catanduanes Reef Break - Aguilar, Maria Cristina M. (Animo Repository, 2015)
The surfing community in the Philippines is rapidly emerging. There are already groups of surfers who dedicate themselves to attract more surfers and have fun with them in different surfing destinations in the Philippines. These groups of surfers specifically Surf4Ezra created the Catanduanes Reef Break (CRB). The CRB is a 3-day simultaneous event of surfing, skateboarding, and music festival. This is an annual event of Surf4Ezra, which takes place every May. Unfortunately, Surf4Ezra was not able to meet their objectives for the event, which is to generate funds for the local surfing community and promote sustainable tourism in Catanduanes. With this, we aim to help them evaluate the previous CRBS (i.e. 2014 and 2015) and create a more viable and profitable plan for future events (e.g., 2016) that will result in the preparation of a teaching case that will be used in marketing courses.